Body Image Discrepancy, Self Esteem and their Impact onAbnormal Eating Attitudes Among Osun State UniversityStudents, Osogbo, Osun State (Western Journal of Medical and Biomedical Sciences, 2025)
This study explores the impact of body image discrepancy and self-esteem on Abnormal eating attitudes among undergraduates. It was a cross-sectional study with descriptive study design, a multistage sampling technique was used to collect data from 247 students. The mean age of respondents was 20.04 ± 2.6 years, with a predominance of females (79.8%). Among participants, 26.3% reported dissatisfaction with their body image, 18.0% had low self-esteem, and 28% were predisposed to abnormal eating attitudes. A significantly higher proportion of participants dissatisfied with their body image (90.2%) exhibited unhealthy eating attitudes compared to 36.1% of those satisfied with their body image, a difference that was statistically significant (p < 0.001). Additionally, 53.4% of students with eating disorders had low self-esteem, while 32.9% and 13.7% exhibited average and high self-esteem, respectively. However, this relationship between self-esteem levels and eating disorders was not statistically significant (p = 0.679). The findings reveal a strong association between body image dissatisfaction and abnormal eating attitudes, highlighting body image as a critical factor in predicting unhealthy eating behaviors among students. However, self-esteem showed no statistically significant relationship with abnormal eating attitudes. These findings underscore the need for targeted interventions addressing body image concerns to promote healthier eating behaviors among undergraduates.
Keywords: Body image; Eating attitudes; Relationship, Self-esteem; Undergraduates